2000
DOI: 10.1042/bst0280250
|View full text |Cite
|
Sign up to set email alerts
|

Immunosenescence: potential causes and strategies for reversal

Abstract: Age-related deterioration in immune function has been recognized in many species. In humans the clinical manifestation of such immune dysfunction is age-related increases in the susceptibility to certain infections and in the incidence of some autoimmune disease and certain cancers. Laboratory investigations reveal age-related changes in the peripheral T cell pool, in the predominant phenotype, cytokine production profiles, signalling function and in replicative ability following stimulus with antigen, mitogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…A number of groups have focused on biochemical/ physiological parameters which are altered with aging, including, but not limited to, factors such as chromosomal telomere length, cellular proteasome function, etc., and asked whether they might contribute to altered immunocompetence [41][42][43]. There is evidence that chronic oxidative stress might contribute to the immunological changes seen [43][44][45], though longevity was not increased by increasing antioxidants in the diet [46].…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups have focused on biochemical/ physiological parameters which are altered with aging, including, but not limited to, factors such as chromosomal telomere length, cellular proteasome function, etc., and asked whether they might contribute to altered immunocompetence [41][42][43]. There is evidence that chronic oxidative stress might contribute to the immunological changes seen [43][44][45], though longevity was not increased by increasing antioxidants in the diet [46].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of therapeutic approaches are being tested, including thymic transplants (72) and restoration of thymic progenitor cells (73, 74) or haematopoietic stem cells (75). In addition, methods such as chemical or physical castration to lower circulating levels of sex hormones (7678) or treatment with IL-7, alone, or in combination with LHRH agonists (67, 79, 80), have been shown to increase the rate of export from the existing, but atrophied, thymus. Finally, growth hormones to increase thymic mass (81) should be tested, as it has been shown that thymic output correlates with the size of the thymus and is independent of age (22).…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition is common in the aged population, and a lower serum folate level has been correlated with decreased proliferation of T cells from elderly subjects [21]. A higher response to mitogens in vitro has been demonstrated to be associated with reduced infections [22] and a better response to vaccine [3], suggesting a physiological effect of this observation. Differences were observed between groups in the types of cells present in the spleen and MLNs.…”
Section: Reduced Mitogen Response In the Spleen And Mlnsmentioning
confidence: 96%